The Occurrence and Prevalence of Time Domain Structures in the Kelvin-Helmholtz Instability at Different Positions Along the Earth’s Magnetospheric Flanks - Wilder, F. D.; Ergun, R. E.; Gove, D.; Eriksson, S.; Hansel, P.; Ahmadi, N.; Malaspina, D. M.; Burch, J. L.; Torbert, R. B.; Strangeway, R. J.; Giles, B. L. (Frontiers in Astronomy and Space Sciences, 2021)
The Kelvin-Helmholtz instability (KHI) is thought to be an important driver for mass, momentum, and energy transfer between the solar wind and magnetosphere. This can occur through global-scale “viscous-like” interactions, as well as through local kinetic processes such as magnetic reconnection and turbulence. An important aspect of these kinetic processes for the dynamics of particles is the electric field parallel to the background magnetic field. Parallel electric field structures that can occur in the KHI include the reconnection electric field of high guide field reconnection, large amplitude ion acoustic waves, as well as time domain structures (TDS) such as double layers and electrostatic solitary waves. In this study, we present a survey of parallel electric field structures observed during three Kelvin Helmholtz events observed by NASA’s Magnetospheric Multiscale (MMS), each at different positions along the magnetosphere’s dusk flank. Using data from MMS’s on-board solitary wave detector (SWD) algorithm, we statistically investigate the occurrence of TDS within the KHI events. We find that early in the KHI development, TDS typically occur in regions with strong field-aligned currents (FACs) on the magnetospheric side of the vortices. Further down the flanks, as the vortices become more rolled up, the prevalence of large electric currents decreases, as well as the prevalence of SWDs. These results suggest that as the instability develops and vortices grow in size along the flanks, kinetic-scale activity becomes less prevalent.